(untitled) (Journal of Naval Architecture and Marine Engineering, 2018)
The realistic flow on each blade of the front and rear propellers with contra-rotating propellers (CRPs) are most complex because that consist the interaction forces with themselves and it affects to the actual efficiency of the propeller blades. The wake of CRPs at the gap between the front and rear propellers have influent to the variation of propeller performance for the front and rear propellers. So, this paper presented the numerical simulation of propeller performance on CRPs with steady method in the first. Second, it is applied to evaluate the propeller performance with unsteady method in time accuracy including investigating the wake on a transverse plane between the front and rear propellers and a transverse plane located downstream of the rear propeller. The wake was analyzed through velocity vector magnitude contours. The numerical simulations were conducted using the Reynolds Averaged Navier-Stokes (RANS). The calculation results have been compared the measurement data.